2018
DOI: 10.1016/j.gca.2018.03.015
|View full text |Cite
|
Sign up to set email alerts
|

The silicon isotopic composition of fine-grained river sediments and its relation to climate and lithology

Abstract: The d 30 Si stable isotopic composition of silicon in soils and fine-grained sediments can provide insights into weathering processes on continents, with important implications on the Si budget of modern and past oceans. To further constrain the factors controlling the distribution of Si isotopes in sediments, we have analysed a large number (n = 50) of separate size-fractions of sediments and suspended particulate materials collected near the mouth of rivers worldwide. This includes some of the world's larges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 67 publications
(88 reference statements)
2
17
0
Order By: Relevance
“…Similar incongruency might affect riverine Ge/Si diss , δ 30 Si diss , and δ 74 Ge diss of the Watson River, potentially invalidating the modeling results here, given that the model assumes congruent dissolution of primary minerals. However, it is notable that using a global riverine clay dataset Bayon et al (2018) have suggested limited δ 30 Si fractionation in cold and arid environments, in agreement with our results from West Greenland. Overall, it appears that glacial weathering results in distinct geochemical and isotopic signatures in streams, and further research is needed to understand the mechanisms responsible.…”
Section: Again Excluding Sample Kl09 Neither F Sisupporting
confidence: 91%
See 1 more Smart Citation
“…Similar incongruency might affect riverine Ge/Si diss , δ 30 Si diss , and δ 74 Ge diss of the Watson River, potentially invalidating the modeling results here, given that the model assumes congruent dissolution of primary minerals. However, it is notable that using a global riverine clay dataset Bayon et al (2018) have suggested limited δ 30 Si fractionation in cold and arid environments, in agreement with our results from West Greenland. Overall, it appears that glacial weathering results in distinct geochemical and isotopic signatures in streams, and further research is needed to understand the mechanisms responsible.…”
Section: Again Excluding Sample Kl09 Neither F Sisupporting
confidence: 91%
“…3a,b) -the opposite from an expected weathering signal but expected if hydrodynamic sorting is affecting the bedload composition. Quartz, although not measured in this location, typically has the lowest Ge/Si ratios of all silicate minerals (Mortlock & Froelich, 1987;Kurtz et al, 2002) and higher δ 30 Si relative to fine sediments (Bayon et al, 2018) and becomes progressively enriched in the river bedload relative to the suspended load during downstream transport (Bouchez et al, 2011), explaining the distinctive trend with elevation in Ge/Si and δ 30 Si compositions.…”
Section: Ge and Si Isotope Composition Of River-transported Solids Inmentioning
confidence: 77%
“…1C). In terms of geological setting, the northern and eastern parts of the Congo Basin are dominated by Archaean and Proterozoic metamorphic basement rocks, while the southwestern part of the watershed is mostly composed of Mesozoic and Cenozoic sedimentary rocks (Bayon et al, 2018). Neogene volcanic rocks associated with the East African Rift system are also encountered in the eastern part of the basin.…”
Section: The Congo Basin: Climate Geological Setting and Land Cover mentioning
confidence: 99%
“…In addition to marine system, the variation of δ 30 Si could help us evaluate the silicon budgets in terrestrial aqueous systems. After the pioneering works on the δ 30 Si of dissolved silicic acid in oceans, rivers, and estuaries [46], the δ 30 Si distributions in various fluids have been clarified, such as freshwater (i.e., −0.1 to +3.4‰) [18,26,46,49,50,51,112,118,141,148,149,150,151], groundwater (−1.43 to +0.43‰) [51], and seawater (i.e., +0.4 to +3.1‰) [13,19,46,47,140,152]. As discussed above, the preferential uptake of light Si isotopes into soil clays and organisms leads to predominately positive Si isotope signatures in continental surface waters.…”
Section: Silicon Isotope Fractionations Linked To Silicon Coordinamentioning
confidence: 99%